Excretory/secretory products from Trichinella spiralis adult worms ameliorate myocardial infarction by inducing M2 macrophage polarization in a mouse model - Lingqin Wu; Wenhui Yin; Jutai Wen; Shuying Wang; Huihui Li; Xiaoli Wang; Weixiao Zhang; Shuyao Duan; Qiuyu Zhu; Erhe Gao; Shili Wu; Bin Zhan; et al. (Parasites & Vectors, 2023)
Abstract Background Ischemia-induced inflammatory response is the main pathological mechanism of myocardial infarction (MI)-caused heart tissue injury. It has been known that helminths and worm-derived proteins are capable of modulating host immune response to suppress excessive inflammation as a survival strategy. Excretory/secretory products from Trichinella spiralis adult worms (Ts-AES) have been shown to ameliorate inflammation-related diseases. In this study, Ts-AES were used to treat mice with MI to determine its therapeutic effect on reducing MI-induced heart inflammation and the immunological mechanism involved in the treatment. Methods The MI model was established by the ligation of the left anterior descending coronary artery, followed by the treatment of Ts-AES by intraperitoneal injection. The therapeutic effect of Ts-AES on MI was evaluated by measuring the heart/body weight ratio, cardiac systolic and diastolic functions, histopathological change in affected heart tissue and observing the 28-day survival rate. The effect of Ts-AES on mouse macrophage polarization was determined by stimulating mouse bone marrow macrophages in vitro with Ts-AES, and the macrophage phenotype was determined by flow cytometry. The protective effect of Ts-AES-regulated macrophage polarization on hypoxic cardiomyocytes was determined by in vitro co-culturing Ts-AES-induced mouse bone marrow macrophages with hypoxic cardiomyocytes and cardiomyocyte apoptosis determined by flow cytometry. Results We observed that treatment with Ts-AES significantly improved cardiac function and ventricular remodeling, reduced pathological damage and mortality in mice with MI, associated with decreased pro-inflammatory cytokine levels, increased regulatory cytokine expression and promoted macrophage polarization from M1 to M2 type in MI mice. Ts-AES-induced M2 macrophage polarization also reduced apoptosis of hypoxic cardiomyocytes in vitro. Conclusions Our results demonstrate that Ts-AES ameliorates MI in mice by promoting the polarization of macrophages toward the M2 type. Ts-AES is a potential pharmaceutical agent for the treatment of MI and other inflammation-related diseases. Graphical Abstract